Chronic Obstructive Pulmonary Disease Is an Independent Predictor for 30-Day Complications and Readmissions Following 1- to 2-Level Anterior Cervical Discectomy and Fusion. Issue 3 (May 2019) - Malik, Azeem Tariq; Jain, Nikhil; Kim, Jeffery; Khan, Safdar N.; Yu, Elizabeth
Study Design: Retrospective cohort. Objectives: To study evidence to assess the impact of chronic obstructive pulmonary disease (COPD) on 30-day outcomes following 1- to 2-level anterior cervical discectomy and fusion (ACDF). Methods: The 2015-2016 American College of Surgeons-National Surgical Quality Improvement Program (ACS-NSQIP) database was queried using Current Procedural Terminology (CPT) codes 22 551 (single-level) and 22 552 (additional level). Patients undergoing disc arthroplasty, multilevel (>2) fusion, posterior cervical spine surgery, and patients with fracture, tumor, and/or infection were excluded. Results: Out of 14 835 patients undergoing an elective 1- to 2-level ACDF, 649 (4.4%) had a diagnosis of COPD at the time of the surgery. Following adjusted logistic regression analysis, prior history of COPD was significantly associated with a longer length of stay (odds ratio [OR] 1.25 [95% confidence interval (CI0 1.04-1.52]; P = .019), superficial surgical site infection (OR 2.68 [95% CI 1.06-6.80]; P = .038), discharge destination other than home (OR 1.49 [95% CI 1.05-2.12]; P = .026), pneumonia (OR 4.37 [95% CI 2.42-7.88]; P < .001), ventilator use >48 hours (OR 5.34 [95% CI 1.88-15.15]; P = .002), unplanned reintubation (OR 3.36 [1.48-7.62]; P = .004), and 30-day readmissions (OR 1.69 [95% CI 1.20-2.38]; P = .003). Conclusions: The findings of this study show that COPD patients are more likely to have postoperative complications and 30-day readmissions, despite elective ACDF itself being a low-risk surgery in general. Results show that majority of the complications were pulmonary in nature, further stressing the need for accurate medical optimization following surgery in these patients.